1999
DOI: 10.2169/internalmedicine.38.512
|View full text |Cite
|
Sign up to set email alerts
|

Human T Cell Leukemia Virus Type I-associated Myelopathy in a Patient with Systemic Lupus Erythematosus.

Abstract: A case of human T cell leukemia virus type I (HTLV-1) associated myelopathy (HAM)/tropical spastic paraparesis (TSP) with 14-year history of systemic lupus erythematosus (SLE) is reported. For 9 years, the numbness of the feet and sacral region progressed with occasional urinary incontinence and constipation. She was admitted to hospital due to gait disturbance and aggravation of SLEand the diagnosis of HAM/TSP was confirmed, indicating that HTLV-1infec-tion is associated with the development of not only HAM/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Both in humans [12][13][14]18] and in mice [15,16], the results of previous research have suggested the involvement of C-type retroviruses, including HTLV-1, in the pathogenesis of SLE. While SLE with ATL or HAM is rare in the clinical setting, several reports have described these comorbidities [19][20][21][22]26]. Compared with the previous cases, the most pathognomonic features of this patient are that his renal pathology showed lupus nephritis and marked T-lymphocyte infiltration into the interstitium (Figs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Both in humans [12][13][14]18] and in mice [15,16], the results of previous research have suggested the involvement of C-type retroviruses, including HTLV-1, in the pathogenesis of SLE. While SLE with ATL or HAM is rare in the clinical setting, several reports have described these comorbidities [19][20][21][22]26]. Compared with the previous cases, the most pathognomonic features of this patient are that his renal pathology showed lupus nephritis and marked T-lymphocyte infiltration into the interstitium (Figs.…”
Section: Discussionmentioning
confidence: 64%
“…The mechanism underlying how HTLV-1 causes SLE remains elusive, but the postulated roles for such retroviruses in the etiopathogenesis of SLE are considered to include intrinsic effects, mimicry of antigens, and/or effects as stimulators of autoimmunity [17,18]. In fact, there have been previous case reports of patients with SLE and ATL [19,20], SLE and HAM [21,22], and SLE and the persistent carrier state of HTLV-1 infection [23]. We herein report the first case in which a kidney biopsy revealed lupus nephritis with interstitial nephritis that might partly include oncogenic T lymphocytes in an HTLV-1 positive patient.…”
Section: Introductionmentioning
confidence: 99%
“…The association between HTLV-1 and scleroderma is also rare [16]. Although some investigators have described an association between HTLV-1 and SLE [17][18][19][20], others have described a negative association between HTLV-1 and SLE [21,22]. Therefore, the precise association between HTLV-1 and various autoimmune diseases has not been fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Вместе с тем отмечена частая ассоциация HTLV-1 инфекции с IgA AKJI [17] и синдромом Шегрена [61], что не исключает участие этого вируса в расширении клиничес кой симптоматики у больных СКВ, за счет при соединения HTLV-1 ассоциированной миелопа-тии/тропического спастического парапареза (HAM/TSP) [44].…”
unclassified